2006
DOI: 10.2320/matertrans.47.59
|View full text |Cite
|
Sign up to set email alerts
|

Order-Disorder Transformation in L1<SUB>0</SUB>-FePd Nanoparticles Studied by Electron Diffraction

Abstract: Disappearance of long-range atomic order in 10-nm-sized L1 0 -FePd (Fe-58 at%Pd) nanoparticles has been studied by electron diffraction using a specimen heating stage attached to a transmission electron microscope. Ordered structure is kept at lowest up to 949 K, while the intensity of superlattice reflection abruptly drops at 982 K. The transformation temperature decreases by about 80 K compared to that of the bulk alloy of Fe-58 at%Pd. Nanobeam electron diffraction from a particle shows a particle size depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Compared to the bulk alloy, such temperature was lower by around 80 K for 13.5 nm FePd NPs. 437 The same group employed ED to determine the long-range order (LRO) parameters of two-dimensional epitaxially-grown dispersed mono- crystalline 10 nm L1 0 -FePd NPs. In that case, the very small volume of the 2D sample would hinder the applicability of the usual XRD measurements for the calculation of the LRO parameters.…”
Section: Microscopy Techniques For Np Characterizationmentioning
confidence: 99%
“…Compared to the bulk alloy, such temperature was lower by around 80 K for 13.5 nm FePd NPs. 437 The same group employed ED to determine the long-range order (LRO) parameters of two-dimensional epitaxially-grown dispersed mono- crystalline 10 nm L1 0 -FePd NPs. In that case, the very small volume of the 2D sample would hinder the applicability of the usual XRD measurements for the calculation of the LRO parameters.…”
Section: Microscopy Techniques For Np Characterizationmentioning
confidence: 99%
“…The coreshell structure of the particles was attributed to the order of elemental deposition and the limited annealing time of the particular study (10 min), rather than resulting from an equilibrium two-phase field. Similar nanoparticle depositions by the same authors with longer annealing times, also centered about 58 at % Pd averages, have yielded particles of only the L1 0 phase [64][65][66][67]. These studies provide a picture of how the Pd saturated L1 0 phase will behave magnetically at the nanoscale.…”
Section: -Studies Approaching the Eutectoid Compositionsupporting
confidence: 61%
“…The light tetragonality of L1 0 FePd introduces only a small wrinkle into these orientation relationships, aligning the c-axis preferentially out of the plane for MgO (001) but aligning randomly on MgO (110) and MgO (111) so that they produce four and eight possible L1 0 variants respectively. It is also expected that Fe-Pd will grow epitaxially on NaCl substrates, though this is has only been confirmed by the growth of cube-on-cube nanoparticles and not films [63][64][65][66][67]159]. Most films in the literature are being grown explicitly for their L1 0 magnetic properties, but there is pursuit to achieve shape-memory properties at the Fe 70 Pd 30…”
Section: -Fe-pd Thin Films In Literaturementioning
confidence: 99%
“…3a ). 69,70 Meanwhile, the FePd nanoparticles introduced by Sato et al in 2000 were synthesized by a modified polyol process, showing the thermal treatment effect on magnetic properties. 71 Besides, in 2004 Hou et al reported monodisperse FePd nanoparticles, controlled by the ratio and type of stabilizer, presenting an average diameter of 13.5 nm and an optimal coercivity of 350 Oe, as shown in Fig.…”
Section: Preparation and Magnetic Properties Of Iron-based Ferrous Ma...mentioning
confidence: 99%